Intercultural competence for translators - Tomozeiu, Daniel; Koskinen, Kaisa; D'Arcangelo, Adele (Abingdon, Oxon, [England] Routledge, 2018)
"By definition, translators are intercultural mediators. This book explores some of the most important current approaches in defining intercultural competence for translators. At the same time, it provides real-life examples of different approaches in operationalizing intercultural competence and teaching it in a translator-training context. Written for a global audience, the book provides an informative overview of the field as well as practical examples from different academic and cultural contexts. This book was originally published as a special issue of The Interpreter and Translator Trainer"--Amazon.com.
Includes bibliographical references and index.
Keywords: Translating and interpreting; Translators -- Training of; Intercultural communication